Excision and reintegration of the Escherichia coli K-12 chromosomal element e14. - Brody, H (1985)
The genetic element e14 is a natural component of the Escherichia coli K-12 chromosome. On induction of the SOS pathways, e14 excises as a 14.4-kilobase circle. We report here on the reintegration of e14 into the chromosome of cured (e14 degrees) E. coli K-12 derivatives. Using a Tn10 insertion mutant of e14, we found that reintegration occurred specifically at the locus originally occupied by e14 and with the same orientation. The reintegration event required neither the RecA nor the RecB functions. The attachment site of the free form was located within a 950-base-pair HindIII-AvaI fragment and shared sufficient homology with the host attachment site to form detectable DNA-DNA hybrids. Even though E. coli C and B/5 did not contain e14, they did possess a HindIII restriction fragment that hybridized to the free e14 attachment fragment. E. coli C could be transformed with e14-1272::Tn10, resulting in integration at this site of homology. The Tn10 mutants were also used in mapping the point of e14 attachment. We found the following sequence: fabD purB atte14 umuC. Furthermore, analysis of a recombinant plasmid that contained both the e14 attachment site and the purB locus showed that these two loci occur within 11 kilobases of each other.